Efficient resource allocation in the IEEE 802.11ax network leveraging OFDMA technology - Gazi Zahirul Islam; Mohammod Abul Kashem (Journal of King Saud University: Computer and Information Sciences, 2022)
The IEEE 802.11ax pave the way to deliver the high-speed communications in the Wi-Fi network even in the dense areas. In this regard, the most challenging task is to enhance the throughput as IEEE 802.11ax standard promises to provide four times improvement in average throughput per station. Unfortunately, none of the existing protocols could satisfy the demand of the standard yet. The performance of the IEEE 802.11ax protocol largely depends on the efficient and wise scheduling of resource units to the stations. The uplink scheduling is more challenging than the downlink since in the uplink path many stations send data to the access point where the stations must be synchronized for the OFDMA transmissions. This paper innovates an uplink scheduling protocol named Efficient Resource Allocation (ERA) that promises to provide a high-throughput to the Wireless LAN along with the reduction of retransmissions of the packets. The simulations and analyses show that the proposed protocol would be a robust one to satisfy the promises of the latest IEEE 802.11ax standard. To the best of our knowledge, the proposed protocol is the unique one of its kind where the resource units are distributed to the stations according to their available loads.